Dosimetric feasibility of direct post-operative MR-Linac-based stereotactic radiosurgery for resection cavities of brain metastases. (February 2023) - Seravalli, Enrica; Sierts, Michelle; Brand, Eric; Maspero, Matteo; David, Szabolcs; Philippens, Mariellen E.P.; Voormolen, Eduward H.J.; Verhoeff, Joost J.C.
Highlights: Direct post-operative MR-Linac based radiosurgery is dosimetrically feasible. Advantages of this workflow are increased patient comfort and logistics. Abstract: Background: Post-operative radiosurgery (SRS) of brain metastases patients is typically planned on a post-recovery MRI, 2–4 weeks after resection. However, the intracranial metastasis may (re-)grow in this period. Planning SRS directly on the post-operative MRI enables shortening this time interval, anticipating the start of adjuvant systemic therapy, and so decreasing the chance of extracranial progression. The MRI-Linac (MRL) allows the simultaneous execution of the post-operative MRI and SRS treatment. The aim of this work was investigating the dosimetric feasibility of MRL-based post-operative SRS. Methods: MRL treatments based on the direct post-operative MRI were simulated, including thirteen patients with resectable single brain metastases. The gross tumor volume (GTV) was contoured on the direct post-operative scans and compared to the post-recovery MRI GTV. Three plans for each patient were created: a non-coplanar VMAT CT-Linac plan (ncVMAT) and a coplanar IMRT MRL plan (cIMRT) on the direct post-operative MRI, and a ncVMAT plan on the post-recovery MRI as the current clinical standard. Results: Between the direct post-operative and post-recovery MRI, 15.5 % of the cavities shrunk by > 2 cc, and 46 % expanded by ≥ 2 cc. Although the direct post-operative cIMRT plans had a higher median gradient index (3.6 vs 2.7) and median V3Gy of the skin (18.4 vs 1.1 cc) compared to ncVMAT plans, they were clinically acceptable. Conclusion: Direct post-operative MRL-based SRS for resection cavities of brain metastases is dosimetrically acceptable, with the advantages of increased patient comfort and logistics. Clinical benefit of this workflow should be investigated given the dosimetric plausibility.